The ATLAS(3D) project - V. The CO Tully-Fisher relation of early-type galaxies - Davis, T; Bureau, M; Young, L; Alatalo, K; Blitz, L; Cappellari, M; Scott, N; Bois, M; Bournaud, F; Davies, R; de Zeeuw, P; Emsellem, E; et al. (2011)
We demonstrate here using both single-dish and interferometric observations that CO molecules are an excellent kinematic tracer, even in high-mass galaxies, allowing us to investigate for the first time the CO Tully-Fisher relation (CO-TFR) of early-type galaxies. We compare the TFRs produced using both single-dish and interferometric data and various inclination estimation methods, and evaluate the use of the velocity profile shape as a criterion for selecting galaxies in which the molecular gas extends beyond the peak of the rotation curve. We show that the gradient and zero-point of the best-fitting relations are robust, independent of the velocity measure and inclination used, and agree with those of relations derived using stellar kinematics. We also show that the early-type CO-TFR is offset from the CO-TFR of spirals by 0.98 ± 0.22 mag at Ks band, in line with other results. The intrinsic scatter of the relation is found to be ≈0.4 mag, similar to the level found in the spiral galaxy population. Next-generation facilities such as the Large Millimeter Telescope and the Atacama Large Millimeter/Sub-millimeter Array should allow this technique to be used in higher redshift systems, providing a simple new tool to trace the mass-to-light ratio evolution of the most massive galaxies over cosmic time. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.